2020
DOI: 10.3390/cmd1020007
|View full text |Cite
|
Sign up to set email alerts
|

The Corrosion Performance and Mechanical Properties of Mg-Zn Based Alloys—A Review

Abstract: Magnesium alloys have shown great potential for applications as both structural and biomedical materials due to their high strength-to-weight ratio and good biodegradability and biocompatibility, respectively. Among them, Mg-Zn based alloys are attracting increasing interest for both applications. As such, this article provides a review of the corrosion performance and mechanical properties of Mg-Zn based alloys, including the influence of environment and processing on both of them. The strategies for tailorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…В настоящее время магниевые сплавы рассматриваются, как одни из наиболее перспективных материалов для применения в качестве биорезорбируемых имплантатов в медицинской промышленности [1,2]. Это связано с их уникальным сочетанием свойств: по плотности и модулю Юнга магниевые сплавы наиболее близки к костной ткани человека и, что наиболее важно, они могут постепенно растворяться в организме, не причиняя ему вреда.…”
Section: Introductionunclassified
“…В настоящее время магниевые сплавы рассматриваются, как одни из наиболее перспективных материалов для применения в качестве биорезорбируемых имплантатов в медицинской промышленности [1,2]. Это связано с их уникальным сочетанием свойств: по плотности и модулю Юнга магниевые сплавы наиболее близки к костной ткани человека и, что наиболее важно, они могут постепенно растворяться в организме, не причиняя ему вреда.…”
Section: Introductionunclassified
“…The standard electrode potential of Mg is −2.37 V (SCE), So it is chemically active and vulnerable to erosion damage in acidic, neutral and weak alkaline media, hence the corrosion behavior of Mg metals has been the focus Liu et al, 2019;Jiang et al, 2020). The corrosion behavior of Mg metals has two categories, uniform corrosion and localized corrosion.…”
Section: Corrosion Propertymentioning
confidence: 99%
“…Furthermore, inconsistencies on the effect of extrusion on the corrosion rate also exist. While some authors have reported that extruded Mg alloys exhibit lower corrosion rates than those processed by casting due grain refinement and redistribution of second phases [9,17,18], other independent studies have shown the opposite behavior, as reported in a very informative review on Mg-Zn alloy corrosion by Jiang et al [4]. At this point, it should be commented that the corrosion resistance of as-extruded Mg-Zn alloys produced by powder metallurgy has been highly understudied.…”
Section: Introductionmentioning
confidence: 95%
“…The Al-Zn (AZ) series are among the most widely used Mg alloys. Aluminum is extensively used in Mg alloys as it is a light and soluble element which improves strength and corrosion resistance of Mg [4]. However, Al has been reported to be neurotoxic and its use for biomedical applications is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation